PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT ALAM JAYA GRAHA - Abdullah, Aliah; Army, Widya Lelisa; Rahayu, Tutik (Fakultas Ekonomi dan Bisnis, 2024)
Work discipline is a crucial factor in achieving a company's goals. This study aims to determine the impact of work discipline on employee performance in the Logistics Division of PT Alam Jaya Graha. The company operates in the transportation sector and is based in Bekasi, West Java. The research was conducted using arithmetic mean and simple linear regression methods, with a sample size of 71 respondents and census is adapted. The findings indicate that the average work discipline score is 3.55, which falls into the